The abstinence teacher - Perrotta, Tom, 1961-; Scott, Campbell (New York, N.Y. : Audio Renaissance, 2007)
Ruth Ramsey, the human sexuality teacher at the local high school, butts heads with the soccer coach, Tim Mason, a former addict who became an evangelical Christian after hitting rock bottom.
Unabridged.
Compact discs.
Read by Campbell Scott.
Keywords: Sex educators -- Fiction; Soccer coaches -- Fiction; Evangelists -- Fiction; Divorced parents -- Fiction; Culture conflict -- Fiction; Interpersonal relations -- Fiction; Suburban life -- Fiction; Audiobooks